Various Definitions of Failure Are Used in Studies of Patients Who Underwent Anterior Cruciate Ligament Reconstruction - Levi Aldag, B.S; Johnathan Dallman, B.S; Erik Henkelman, M.D; Ashley Herda, Ph.D; Jeffrey Randall, M.D; Armin Tarakemeh, B.A; Tucker Morey, B.S; Bryan G. Vopat, M.D (Elsevier, 2023)
Purpose: To conduct a literature review to assess the definitions of anterior cruciate ligament reconstruction (ACLR) failure used throughout the orthopaedic literature. Methods: A systematic search of Embase, Ovid Medline, SPORTDiscus, and Web of Science was conducted by a university librarian to identity level I-IV clinical studies on ACLR failure. Inclusion criteria consisted of patients who underwent ACLR and included a definition of failure of ACLR. Patients who underwent anterior cruciate ligament (ACL) repairs, animal/cadaver studies, review studies, non-English language articles, and non-full text articles were excluded. Failure data were extracted from each study and categorized. Other data that were extracted included follow-up time after ACLR, failure reoperation rate, and failure reoperation procedure. Descriptive statistics was used to analyze the data. Results: Out of 2,775 studies, 104 (3.75%) met inclusion criteria and were analyzed in this review. The most common definition of ACLR failure included the use of a physical examination, specifically Lachman's test (21/104 [20.2%]), anterior laxity assessment, or a Pivot-Shift test (24/104 [35.2%]) or undergoing or requiring revision ACLR (39/104 [37.5%]). Although some studies used quantitative tests or imaging to help define "failure," others simply defined it as graft rerupture that was otherwise not defined (22/104 [22.5%]). Other common definitions included: the use of imaging (magnetic resonance imaging/radiographs) to confirm graft re-rupture (37/104 [35.6%]), patient-reported outcomes (recurrent instability)/patient reported outcomes measures (International Knee Documentation Committee [IKDC], Knee injury and Osteoarthritis Outcome Score [KOOS], Tegner) (18/104 [17.3%]), and the use of an arthrometer (KT-1000/2000, Rollimeter, or Kneelax) (17/104 [16.3%]). The least common definitions included graft failure or rerupture confirmed by arthroscopy (13/104 [12.5%]) and nonrevision surgery (2/104 [1.0%]). The failure rate of this procedure ranged from 0% to 100% depending on the definition of "failure." Conclusions: In this study, we found that a variety of definitions of failure are used among studies published in the orthopaedic literature. The most common criteria for failure of ACLR were the results of physical examination tests (35%), the need for undergoing a revision ACLR (36%), and the use of imaging to diagnose the failure (34%). About 17% of studies included in this review used patient-reported outcomes, specifically recurrent instability, or PROMs (IKDC, KOOS, Tegner) in their assessment of failure of ACLR. The least used definitions of "failure" of ACLR included nonrevision ACLR surgery (2%). Although some studies used similar tests or categories in their definition of failure, there were a variety of score and grade cutoff points between them. Level of Evidence: Level IV, systematic review of Level II-IV studies.